2012
DOI: 10.1186/1472-6874-12-32
|View full text |Cite
|
Sign up to set email alerts
|

Mammography-based screening program: preliminary results from a first 2-year round in a Brazilian region using mobile and fixed units

Abstract: BackgroundBreast cancer is the most frequently diagnosed cancer and the leading cause of cancer deaths among women worldwide. The use of mobile mammography units to offer screening to women living in remote areas is a rational strategy to increase the number of women examined. This study aimed to evaluate results from the first 2 years of a government-organized mammography screening program implemented with a mobile unit (MU) and a fixed unit (FU) in a rural county in Brazil. The program offered breast cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Therefore, this region experienced a transition from the diagnostic mammography stage, in which mammograms were often performed in symptomatic patients while the demand for diagnostic exams was suppressed, to a large-scale mammography screening. In the years before this project, the incidence of early tumors (clinical staging 0 + I) in this region was 14.5%; this rate increased to 43.2% among the women who adhered to the project, reflecting a prior deficiency in access to mammography screening [9].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, this region experienced a transition from the diagnostic mammography stage, in which mammograms were often performed in symptomatic patients while the demand for diagnostic exams was suppressed, to a large-scale mammography screening. In the years before this project, the incidence of early tumors (clinical staging 0 + I) in this region was 14.5%; this rate increased to 43.2% among the women who adhered to the project, reflecting a prior deficiency in access to mammography screening [9].…”
Section: Discussionmentioning
confidence: 95%
“…However, there is no organized screening program, and only isolated studies were conducted [8]. A regional pilot screening program was initiated in the countryside of São Paulo State, in which mammography screening was implemented at the population level [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are some well-organized, although isolated, screening programs in the country, such as the one run by the Cancer Hospital of Barretos, in the state of São Paulo, which employs mobile units outfitted with mammography equipment in order to carry out active surveillance of the target population (41,42) .…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as cultural differences, socioeconomic differences, geographical location, and limited information on the part of the population can also impede access to health care services, thus increasing disparity (41,45) . The low rates of mammography coverage found in the present study underscore the need to research the geographic distribution of the mammography equipment available via the SUS and the influence that it can have on access to the test (16,42) .…”
Section: Discussionmentioning
confidence: 99%
“…The Haikel et al (19) study about a screening based program in mammography reported strategies on adherence and better optimization in breast cancer detection using this initiative. For these authors, administrators of public health institutions must be always encouraged to adhere to population level program, which might consequently increase participation of these women.…”
Section: Discussionmentioning
confidence: 99%